2010
DOI: 10.1007/s11259-010-9345-x
|View full text |Cite
|
Sign up to set email alerts
|

High-fat feeding and staphylococcus intermedius infection impair beta cell function and insulin sensitivity in mongrel dogs

Abstract: As obesity is a state of low-grade inflammation, we aimed to investigate the combined effect of high-fat diet and bacterial infection on beta-cell function and insulin sensitivity in dogs. We used 20 healthy, male, mongrel dogs randomly divided into four groups: control group-healthy, non-obese dogs; infected group-non-obese dogs with experimentally induced infection (Staphylococcus intermedius); obese group-obese dogs (after 90 day high-fat diet) and obese-infected group-obese dogs with experimentally induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…5 One study on dogs has demonstrated that the lowest rate of glucose elimination was in a group infected with Staphylococcus intermedius. 8 Infection causes marked changes in whole body glucose metabolism as a result of acceleration in endogenous glucose production, due to increased gluconeogenesis. 9 It has been shown that acute infection in humans causes insulin resistance and glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…5 One study on dogs has demonstrated that the lowest rate of glucose elimination was in a group infected with Staphylococcus intermedius. 8 Infection causes marked changes in whole body glucose metabolism as a result of acceleration in endogenous glucose production, due to increased gluconeogenesis. 9 It has been shown that acute infection in humans causes insulin resistance and glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infection can lead to the impairment in insulin secretion [21] but the system(s) responsible of this effect has not been established. Attractive candidates are the PLA 2 s because their activity during insulin release by b cells.…”
Section: Discussionmentioning
confidence: 99%
“…Participation of PLA 2 s in glucose-induced insulin secretion is reflected by the fact that secretion is impaired by suppressing their expression or by their pharmacologic inhibition [33,34]. Bacterial infection can lead to the impairment in insulin secretion [21] but the system(s) responsible of this effect has not been established. Attractive candidates are the PLA 2 s because their activity during insulin release by b cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overrepresented dog leukocyte antigen gene influences the type 1 diabetes expression, especially on Samoyed dogs and Miniature Poodles [16,31]. Companion animals eat energy-dense diets that induce obesity-related hyperglycemia and impaired glucose tolerance which in turn increase the risk of infection [21,31,37]. …”
Section: Discussionmentioning
confidence: 99%